Functions and Interactions of Mammalian KDM5 Demethylases - Pavlenko, Egor; Ruengeler, Till; Engel, Paulina; Poepsel, Simon (Frontiers in Genetics, 2022)
Mammalian histone demethylases of the KDM5 family are mediators of gene expression dynamics during developmental, cellular differentiation, and other nuclear processes. They belong to the large group of JmjC domain containing, 2-oxoglutarate (2-OG) dependent oxygenases and target methylated lysine 4 of histone H3 (H3K4me1/2/3), an epigenetic mark associated with active transcription. In recent years, KDM5 demethylases have gained increasing attention due to their misregulation in many cancer entities and are intensively explored as therapeutic targets. Despite these implications, the molecular basis of KDM5 function has so far remained only poorly understood. Little is known about mechanisms of nucleosome recognition, the recruitment to genomic targets, as well as the local regulation of demethylase activity. Experimental evidence suggests close physical and functional interactions with epigenetic regulators such as histone deacetylase (HDAC) containing complexes, as well as the retinoblastoma protein (RB). To understand the regulation of KDM5 in the context of chromatin, these interactions have to be taken into account. Here, we review the current state of knowledge on KDM5 function, with a particular emphasis on molecular interactions and their potential implications. We will discuss and outline open questions that need to be addressed to better understand histone demethylation and potential demethylation-independent functions of KDM5s. Addressing these questions will increase our understanding of histone demethylation and allow us to develop strategies to target individual KDM5 enzymes in specific biological and disease contexts.